Couples coping with COPD: exploring (dis)similarity between patients’ and spouses’ psychosocial adjustment - Figueiredo, Daniela (2014)
Being diagnosed and treated for COPD is often associated with emotional distress. Evidence suggests that spouses play a major role in determining patient's psychosocial adjustment. Yet, much less is known about partners' adjustment to COPD demands. This study aimed to explore and compare patients' and spouses' psychosocial adjustment to COPD. A cross-sectional study with a convenience sample was conducted. Socio-demographic data were collected. Psychosocial adjustment was evaluated in seven life domains by the Psychosocial Adjustment to Illness Scale - Self-Report (PAIS-SR). Depression, Anxiety and Stress Scales (DASS) were used to assess emotional status. In both scales, higher scores indicate greater disturbance. Descriptive and inferential analyses were performed. Twenty five dyads of patients with COPD (66.1±9.2yrs, FEV1 53.6±18.5pp) and spouses (63.6±8.7yrs) have participated. Spouses reported more problems in overall psychosocial adjustment (23.9±12.1 vs. 31.6±11.8, p=.042) and psychological distress (6.3±2.6 vs. 3.7±2.8; p=.004). Health care orientation was the life domain with the highest scores in both patients (7.0±2.9) and spouses (8.8±3.3, p=.060). Spouses presented higher levels of depressive (9.6±7.7 vs. 5.4±5.1, p=.027) and stress (14.2±7.5 vs. 9.7±6.5, p=.028) symptoms than patients. High levels of anxiety symptoms were found for both patients and spouses (8.9±5.5 vs. 9.6±6.5, p=.676). Findings suggest that COPD can result in considerable emotional distress for marital couples, in particular, for spouses. Recognising COPD as a family disease is crucial to the development of family-based supportive interventions that can improve couples' healthy adjustment.